2018
DOI: 10.1053/j.jfas.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel Elastic Syndesmosis Hook Plate Fixation Versus Routine Screw Fixation for Syndesmosis Injury

Abstract: Unstable external-rotation type ankle fractures with concomitant syndesmosis injury commonly occur. Syndesmosis screw fixation has long been regarded as a reference standard treatment for syndesmosis injury. However, its complications and biomechanical disadvantages have become controversial; thus, we designed a novel elastic syndesmosis hook plate (ESHP) that combines the features of both rigidity and flexibility. The purpose of the present study was to introduce this new method and compare its clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…42,50,54,55,57,60 Several studies reported patients being non-weight-bearing until fracture healing was confirmed with radiographic evidence. 49,51,56,57,60 Those studies that included separate cohorts with and without syndesmotic injury or repair 42,49,50,55 specified longer periods before full weight-bearing in patients with syndesmotic injury, usually 8-12 weeks compared with 4 to 6 weeks in patients without syndesmosis disruption.…”
Section: Weight-bearingmentioning
confidence: 99%
“…42,50,54,55,57,60 Several studies reported patients being non-weight-bearing until fracture healing was confirmed with radiographic evidence. 49,51,56,57,60 Those studies that included separate cohorts with and without syndesmotic injury or repair 42,49,50,55 specified longer periods before full weight-bearing in patients with syndesmotic injury, usually 8-12 weeks compared with 4 to 6 weeks in patients without syndesmosis disruption.…”
Section: Weight-bearingmentioning
confidence: 99%
“…Six were excluded because they were comparative studies without randomization, while 5 reports from clinicaltrials.gov were excluded because 1 RCT was ongoing at the time of the search, 1 was complete but with no report of the results, and 3 referred to RCTs already completed and published. So, after the application of inclusion and exclusion criteria, 7 studies 1,4,5,18,19,21,41 were included in the final analysis ( Figure 1).…”
Section: Article Selectionmentioning
confidence: 99%
“…3,14,17,23,28,31,42 However, the most recent meta-analysis—by Chen et al, 3 which comprised 9 studies and 387 patients—was seriously biased by the limited overall quality owing to the inclusion of prospective and retrospective studies with only 3 randomized controlled trials (RCTs). 4,18,19 The great interest in the treatment of syndesmotic injuries is confirmed by the fact that several new RCTs have been performed in Europe, 1,5,24 Canada, 27 and Asia 41 in the past few years.…”
mentioning
confidence: 99%
“…Alternative methods for treatment of unstable syndesmotic injuries reported in literature include syndesmotic hooks or hook plates [45,160,166], transfixation bolts [162], various suture button constructs [5,8,38,94,95,106,117,120,131,132,141,142,165], ligament bracing [58,80,98,119,135,140], tendon autograft [25,56,91,98] or even allograft reconstruction [35]. During the last decades, several studies have clearly shown superior results after flexible dynamic syndesmotic stabilization compared to the use of syndesmotic screws with regard to accuracy of reduction, functional outcome, and even development of posttraumatic ankle arthritis [9,32,34,48,57,72,76,94,111,124,134,171].…”
Section: Introductionmentioning
confidence: 99%